Incidence, clinical features and perinatal outcome in anomalous fetuses with late‐onset growth restriction: cohort study. (1st November 2022) - Dall'Asta, A.; Stampalija, T.; Mecacci, F.; Ramirez Zegarra, R.; Sorrentino, S.; Minopoli, M.; Ottaviani, C.; Fantasia, I.; Barbieri, M.; Lisi, F.; Simeone, S.; Castellani, R.; et al.
ABSTRACT: Objective: To describe the incidence, clinical features and perinatal outcome of late‐onset fetal growth restriction (FGR) associated with genetic syndrome or aneuploidy, structural malformation or congenital infection. Methods: This was a retrospective multicenter cohort study of patients who attended one of four tertiary maternity hospitals in Italy. We included consecutive singleton pregnancies between 32 + 0 and 36 + 6 weeks' gestation with either fetal abdominal circumference (AC) or estimated fetal weight < 10 th percentile for gestational age or a reduction in AC of > 50 percentiles from the measurement at an ultrasound scan performed between 18 and 32 weeks. The study group consisted of pregnancies with late‐onset FGR and a genetic syndrome or aneuploidy, structural malformation or congenital infection (anomalous late‐onset FGR). The presence of congenital anomalies was ascertained postnatally in neonates with abnormal findings on antenatal investigation or detected after birth. The control group consisted of pregnancies with structurally and genetically normal fetuses with late‐onset FGR. Composite adverse perinatal outcome was defined as the presence of at least one of stillbirth, 5‐min Apgar score < 7, admission to the neonatal intensive care unit (NICU), need for respiratory support at birth, neonatal jaundice and neonatal hypoglycemia. The primary aims of the study were to assess the incidence and clinical features of anomalous late‐onset FGR, and to compare the perinatal outcome of such cases with that of fetuses with non‐anomalous late‐onset FGR. Results: Overall, 1246 pregnancies complicated by late‐onset FGR were included in the study, of which 120 (9.6%) were allocated to the anomalous late‐onset FGR group. Of these, 11 (9.2%) had a genetic syndrome or aneuploidy, 105 (87.5%) had an isolated structural malformation, and four (3.3%) had a congenital infection. The most frequent structural defects associated with late‐onset anomalous FGR were genitourinary malformations (28/105 (26.7%)) and limb malformation (21/105 (20.0%)). Compared with the non‐anomalous late‐onset FGR group, fetuses with anomalous late‐onset FGR had an increased incidence of composite adverse perinatal outcome (35.9% vs 58.3%; P < 0.01). Newborns with anomalous, compared to those with non‐anomalous, late‐onset FGR showed a higher frequency of need for respiratory support at birth (25.8% vs 9.0%; P < 0.01), intubation (10.0% vs 1.1%; P < 0.01), NICU admission (43.3% vs 22.6%; P < 0.01) and longer hospital stay (median, 24 days (range, 4–250 days) vs 11 days (range, 2–59 days); P < 0.01). Conclusions: Most pregnancies complicated by anomalous late‐onset FGR have structural malformations rather than genetic abnormality or infection. Fetuses with anomalous late‐onset FGR have an increased incidence of complications at birth and NICU admission and a longer hospital stay compared with fetuses with isolated late‐onset FGR. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology. Abstract : Linked article: There is a comment on this article by Li and Lei. Click here to view the Correspondence.